Stabilizing and Anti-Repressor Elements Effectively Increases Transgene Expression in Transfected CHO Cells - Li, Qin; Yan, Rui-Fang; Yang, Yong-Xiao; Mi, Chun-liu; Jia, Yan-long; Wang, Tian-Yun (Frontiers in Bioengineering and Biotechnology, 2022)
Chinese hamster ovary (CHO) cells are currently the most widely used host cells for recombinant therapeutic protein (RTP) production. Currently, the RTP yields need to increase further to meet the market needs and reduce costs. In this study, three stabilizing and anti-repressor (SAR) elements from the human genome were selected, including human SAR7, SAR40, and SAR44 elements. SAR elements were cloned upstream of the promoter in the eukaryotic vector, followed by transfection into CHO cells, and were screened under G418 pressure. Flow cytometry was used to detect enhanced green fluorescent protein (eGFP) expression levels. The gene copy numbers and mRNA expression levels were determined through quantitative real-time PCR. Furthermore, the effect of the stronger SAR elements on adalimumab was investigated. The results showed that transgene expression levels in the SAR-containing vectors were higher than that of the control vector, and SAR7 and SAR40 significantly increased and maintained the long-term expression of the transgene in CHO cells. In addition, the transgene expression level increase was related with gene copy numbers and mRNA expression levels. Collectively, SAR elements can enhance the transgene expression and maintain the long-term expression of a transgene in transfected CHO cells, which may be used to increase recombinant protein production in CHO cells.